Effectiveness of horticulture therapy on depression - Moshfeghi, golnaz; Rezabakhsh, hossein; Danesh, esmat (Advances in Nursing & Midwifery, 2015)
Background and aim: Population ageing and its consequences has become a major concern in most countries around the world. The aim of the present study was to evaluate the effect of horticultural therapy on depression in older nursing-homes residents. Method and material : A quasi-experimental with two groups and pre-test post-test design was used. The sample of the study consisted of 44 older adults ,which were randomly assigned to intervention and control group. Participants in intervention group were engaged in a planting, maintaining and harvesting fruits and vegetables program for 3 months . Quantitative data were collected by 14 questions related to symptoms of depression from Lovibond & Lovibond’s (1995) criterion of depression, stress and anxiety (42 questions).The validity and reliability of the questionnaire have been confirmed by Samani and Jokar(1386). Qualitative data were collected by observation. Quantitative data were analyzed by covariance analysis test. Findings: The results showed that horticultural therapy significantly reduces depression scores among participants in intervention group. There was a significant difference in change scores of the depression (p <0 .01) between experimental and control group. Conclusion: Consistent with previous pieces of research, this paper showed that gardening exercises enhance the emotional state of elderlies. This program could be used to reduce aging effects such as depression. Keywords: Nursing home ; Depression; Horticultural therapy; Elderly